2021
DOI: 10.1002/jca.21913
|View full text |Cite
|
Sign up to set email alerts
|

Immunoadsorption in a dog with severe immune mediated hemolytic anemia

Abstract: Immune mediated hemolytic anemia (IMHA) is a life‐threatening disease with severe, acute hemolysis as a result of an autoimmune response directed against erythrocyte surface antigens. In veterinary medicine, IMHA is usually treated with immunosuppressants and often multiple blood transfusions. In human medicine, immunoadsorption (IA) is an established therapy for antibody removal in immune‐mediated diseases. A female, spayed, five‐year‐old, 28 kg Entlebucher Mountain dog was presented with regenerative anemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…There are only two case reports about IA in veterinary medicine. One case report showed a dog with immune-mediated hemolytic anemia successfully treated with IA, and the other one showed a dog with fulminant acquired myasthenia gravis successfully treated with IA [ 12 , 13 ]. The adsorption of IgG and IgM in the Ligasorb ® IA adsorber is unspecific.…”
Section: Discussionmentioning
confidence: 99%
“…There are only two case reports about IA in veterinary medicine. One case report showed a dog with immune-mediated hemolytic anemia successfully treated with IA, and the other one showed a dog with fulminant acquired myasthenia gravis successfully treated with IA [ 12 , 13 ]. The adsorption of IgG and IgM in the Ligasorb ® IA adsorber is unspecific.…”
Section: Discussionmentioning
confidence: 99%
“…In the veterinary literature, IA has yet not been described for the treatment of neurological disorders. A case report of successful treatment of a dog with immune-mediated hemolytic anemia is the only reference applying IA in dogs [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The indication for IA is a severe myasthenic crisis, or before surgery in patients with thymoma [ 26 ]. In veterinary medicine, IA was successfully used in the management of immune-mediated hemolytic anemia in a dog [ 27 ]. To the best knowledge of the authors, IA has yet not been reported in the veterinary literature for the treatment of acquired MG.…”
Section: Introductionmentioning
confidence: 99%